A comparison of the effectiveness of predictors of caudal block in children-swoosh test, anal sphincter tone, and heart rate response - Nandini M Dave; Madhu Garasia (Wolters Kluwer Medknow Publications, 2012)
Objective: To study the effectiveness of three predictors of successful caudal block in children, viz. swoosh test, heart rate response to injection, and laxity of anal sphincter tone. Aim: To improve the success rates of caudal block in children by identifying the best predictor. Background: Caudal blocks in children are placed after induction of anesthesia. Although simple to learn and perform, the success rate of the blocks may be variable especially in teaching hospitals where trainee anesthetists perform these blocks. Materials and Methods: 223 patients, aged 2-12 years, undergoing lower abdominal and urologic surgery were studied. 0.25% Bupivacaine was administered after induction of general anesthesia according to the Armitage regimen. Results: The sensitivity and specificity were highest with the sphincter tone test (sensitivity 95.22%, specificity 92.86%), followed by the heart rate response (sensitivity 92.82%, specificity 78.57%) and the swoosh test (sensitivity 66.51%, specificity 35.71%). The anal sphincter tone test had the highest positive predictive value (99.5%) and positive likelihood ratio (13.33). The heart rate response had a positive predictive value of 98.48% and a positive likelihood ratio of 4.33. The swoosh test, in our study, had a positive predictive value of 93.92% and a positive likelihood ratio of 1.035. Conclusion: The anal sphincter tone test was the best predictor of successful caudal block. We recommend the use of these additional simple predictors of accurate needle placement to increase the success rate of caudal block especially in teaching hospitals.